The 100 Most Cited Articles in Gerodontology: Bibliometric Analysis - Genaro, Luis Eduardo (2026)
This study evaluated the characteristics of the 100 most-cited papers on gerodontology through bibliometric metrics, focusing on understanding the international production of knowledge. Papers on gerodontology were selected based on their titles and scopes from the Web of Science Core Collection (WoS-CC) database between January 1st and January 31st, 2025. Additional comparisons were conducted in the Scopus and Google Scholar databases. Several bibliometric parameters were extracted, including title, number of citations, citation density, country of origin of the first author, year of publication, study design, and addressed topic. The VOSviewer software was used to create graphical bibliometric maps. The screening process identified 2,730 papers in the WoS-CC database, of which the 100 most-cited papers totaled 10,813 citations, ranging from 62 to 289 citations per paper. The most cited article, by Petersen (2010), accumulated a total of 1,264 citations across the three databases analyzed in the study. Cross-sectional studies were the most frequent (n=32), followed by reviews (n=14), with health services research being the category with the highest citation-per-paper ratio (276.11). In total, 324 researchers contributed to these studies, with Locker, D., being the most-cited author. Community Dentistry and Oral Epidemiology was the most frequent journal among the top 100 most cited publications. Geographically, Europe led the publications (46 papers). Based on the 100 most cited articles, it is evident that research in gerodontology is predominantly characterized by cross-sectional studies. These studies have had a significant impact on healthcare services research. Future implications suggest the need for more longitudinal studies to better understand the long-term effects of interventions in geriatric dentistry. Additionally, there is a growing need for research that integrates diverse methodologies and explores the effectiveness of oral health strategies across different cultural and socioeconomic contexts.